On peer effects: Contagion of pro- and anti-social behavior and the role of social cohesion - Eugen Dimant (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2017)
Little is known about the underlying mechanisms of behavioral contagion, in particular with respect to differences in contagion of pro- versus anti-social behavior. Our principal contribution is the use of a novel experimental approach that enables us to analyze the contagion of behavior under varied levels of social distance to peers and differences in contagion of pro- and anti-social behavior. Anti-social behavior is found to be more contagious and social distance particularly drives the contagion of anti-social but not prosocial behavior. The results yield policy implications with regards to designing effective nudges and interventions to facilitate (reduce) pro- (anti-)social behavior, in both social and work environments.
Keywords: C91; D03; D64; D81; 330; anti-social behavior; behavioral contagion; charitable giving; peer effects